Differential replication and DNA elimination in the polytene chromosomes of Euplotes crassus. - Frels, J S (1996)
The transposon-like Tec elements of Euplotes crassus are precisely excised during formation of polytene chromosomes in the developing macronucleus. To determine whether all Tec elements exhibit identical developmental timing of excision, we used polymerase chain reaction to visualize amplification and diminution at numerous randomly selected Tec insertion sites. Two classes of sites are evident. Early replicating sites show one or more rounds of amplification and diminution (corresponding to excision) and frequently occur within macronuclear-destined sequences. Late replicating sites do not undergo diminution until chromosome fragmentation and are predominantly associated with eliminated sequences. We conclude that the previously described clustering of macro-nuclear-destined sequences in the micronuclear genome allows for their differential replication at the polytene stage and results in targeting of these sequences for transcriptional activation and highly specific deletion and chromosome fragmentation processes.